2021
DOI: 10.3390/su13041933
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Evaluation and Selection Strategies for Green Portfolios under Different Risk Appetites

Abstract: Since investors have diverse risk motives for green investments, this paper uses data envelopment analysis (DEA) and simulation to accurately evaluate the efficiency of green portfolios from the perspective of investors’ subjective risks and accordingly provide suitable investment selection strategies. On the one hand, the paper integrates investors’ risk preferences with efficiency evaluation models under the framework of behavioral finance, and then constructs a green portfolio efficiency evaluation model ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…ESG portfolios (Bertolotti, 2020; Ouchen, 2021) such as green (Anquetin et al, 2022; Yu et al, 2021) and sustainable (Arribas et al, 2019; Khan et al, 2020) portfolios do not leave aside traditional considerations of risk and return, but they are also influenced by emotional, psychological, and cognitive investor considerations (Nofsinger, 2017). Authors such as Beal et al (2005), Bollen (2007), Lewis and Mackenzie (2000), and Williams (2007) showed how personal values influence responsible investors' portfolio selection, generating for them what Ainsworth et al (2018) called psychic dividends, even giving up some profitability to meet their objectives.…”
Section: Theoretical Framework and Research Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…ESG portfolios (Bertolotti, 2020; Ouchen, 2021) such as green (Anquetin et al, 2022; Yu et al, 2021) and sustainable (Arribas et al, 2019; Khan et al, 2020) portfolios do not leave aside traditional considerations of risk and return, but they are also influenced by emotional, psychological, and cognitive investor considerations (Nofsinger, 2017). Authors such as Beal et al (2005), Bollen (2007), Lewis and Mackenzie (2000), and Williams (2007) showed how personal values influence responsible investors' portfolio selection, generating for them what Ainsworth et al (2018) called psychic dividends, even giving up some profitability to meet their objectives.…”
Section: Theoretical Framework and Research Hypothesismentioning
confidence: 99%
“…ESG portfolios (Bertolotti, 2020;Ouchen, 2021) such as green (Anquetin et al, 2022;Yu et al, 2021) and sustainable (Arribas et al, 2019;Khan et al, 2020) portfolios do not leave aside traditional considerations of risk and return, but they are also influenced by emotional, psychological, and cognitive investor considerations (Nofsinger, 2017). Authors such as Beal et al (2005)…”
Section: Responsible Investment Portfolios and Psychic Dividendsmentioning
confidence: 99%
“…Then, they tested this approach through a real-world application on the European market. In parallel with the above study, (Yu et al, 2021) have selected the most promising assets according to their ESG score from the Chinese stock market to construct an ethical CPT-based portfolio. While these literature contributions build on deterministic quantities of sustainability (e.g., the ESG scores), (Dorfleitner and Utz, 2012) have introduced the concept of sustainable returns obtained from firms' ESG scores.…”
Section: Introductionmentioning
confidence: 99%
“…Then, we find the optimal portfolio weights according to the CPT-based asset allocation strategy. This approach generalizes the studies (Yu et al, 2021) and (Liagkouras et al, 2022). In the second model, we account for investors who could be sensitive to the ESG scores and the evolution of these values over time.…”
Section: Introductionmentioning
confidence: 99%
“…Cuando se seleccionan activos usando simultáneamente criterios financieros y ESG, se conforma un portafolio "responsable", también llamado en la literatura portafolio ESG(Bertolotti, 2020;Ouchen, 2021) verde(Anquetin et al, 2022;Yu et al, 2021) o sostenible(Arribas et al, 2019;Khan et al, 2020). Esto implica que los portafolios responsables no dejan de lado el análisis de las variables financieras tradicionales de riesgo y rentabilidad, sino que agregan consideraciones sobre el desempeño ESG de las empresas, según las preferencias individuales del inversionista.La construcción de portafolios responsables incluye, entonces, elementos característicos de la optimización convencional, como la definición previa de una política de inversión, la determinación de objetivos de corto y largo plazo, el cálculo de riesgo y rentabilidad históricas, el análisis de las características del mercado, así como la evaluación del grado de tolerancia al riesgo, los cuales se evalúan a la luz de las consideraciones ESG.…”
unclassified